2003
DOI: 10.1097/00007435-200302000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Sexual Behavior and Sexual Identity in Street Outreach Samples of Four Racial/Ethnic Groups

Abstract: Data indicate the importance of designing and targeting HIV risk interventions and clinical screening, based on behavior and not reported sexual identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 3 publications
4
44
1
2
Order By: Relevance
“…Although some discordance between sexual identity and sexual behavior is to be expected in any population and has been described in the context of nonrandom samples (13,16,18), our analysis suggests a larger discrepancy than has been noted previously in population-based studies. The Urban Men's Health Study (UMHS) (25) included a large probability sample of men who have sex with men, of whom only 3% perceived themselves as heterosexual.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Although some discordance between sexual identity and sexual behavior is to be expected in any population and has been described in the context of nonrandom samples (13,16,18), our analysis suggests a larger discrepancy than has been noted previously in population-based studies. The Urban Men's Health Study (UMHS) (25) included a large probability sample of men who have sex with men, of whom only 3% perceived themselves as heterosexual.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous research has found discordance between selfreported sexual identity and sexual behavior in men (11)(12)(13). Several reports (14 -22) have focused on risk behaviors among men who have sex with men and acknowledge having male sexual partners but do not report a gay identity.…”
mentioning
confidence: 99%
“…Completion of the questionnaire took approximately five minutes. More details on the study are provided elsewhere (Essien et al 3 ; Ross et al 4 , and Essien et al 5 ). The study was approved by the appropriate university human subjects review board.…”
Section: Methodsmentioning
confidence: 99%
“…The questions did not define the meaning of "down low" because we were interested in describing the characteristics of men who identified with this term as they defined it for themselves. This decision was based in part on prior research showing that sexual practices do not necessarily correspond to the labels that individuals use to describe their sexual identity (Ross, Essien, Williams, and Frenandez-Esquer, 2003) and is supported by a recent commentary calling for the use of self-defined labels when working with sexual-minority groups (Young and Meyer, 2005). Further, given the lack of data on DL MSM, we were concerned that providing a definition based on race/ethnicity, gay identity, and/or behavior might inappropriately exclude some men who identify themselves as DL or include others who do not consider themselves to be on the DL.…”
Section: Identification As Down Lowmentioning
confidence: 99%